PEMBENTUKAN POSYANDU MILENIAL DENGAN SISTEM HYBRID: LURING DARING (PRO DARA 119) - Anjaswarni, Tri; Winarni, Sri; Suyanto, Edy (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2023)
Millennial Posyandu with Hybrid system, is a necessity and a challenge in today's technological era. The technology and youth are two sides that cannot be separated. Teenagers need technology and technology that facilitates their developmental needs. In the development of the health sector, the role of adolescents is central because they are figures who will continue to lead the nation. Youth as health cadres and the formation of Millennial Posyandu are important as a form of their participation in health development. The purpose was to develop youth health cadres and Millennial Posyandu which is carried out in a hybrid system through Pro Dara 119. A method was carried out in 5 stages 1) Selection of prospective youth health cadres; 2) Formation of cadres; 3) Assistance program; 4) Training and 5) Implementation of a hybrid millennial Posyandu. Results: Adolescent health cadres were formed in the Bareng and Tanjungrejo sub-districts with 12 cadres each graduating by the lurah, and youth assistants who provided assistance from the beginning of cadre formation to implementation of Posyandu activities. After training in posyandu with 5 table system, the ability of youth health cadres increased. Posyandu were held 2 times in September and October 2021, although the number of in person visits is still very low and Pro dara 119 is not yet effective. Suggestion: Need continuous motivation and support from community leaders and ongoing assistance so that a routine and sustainable millennial Posyandu is implemented. Adolescents self confidence also needs to be continuously improved so that they can provide optimal services.